Transcriptomic and metabolomic-based revelation of the effect of fresh corn extract on meat quality of Jingyuan chicken - Jinli Tian; Yanxu Wu; Wei Zhao; Guojun Zhang; Hu Zhang; Lin Xue; Lijuan Yang; Tong Zhang; Yaling Gu; Juan Zhang (Poultry Science)
To investigate the effect of fresh corn extract (FCE) on chicken meat quality, 135-day-old Jingyuan chicken hens were fed diets containing different doses of FCE (CON, 0.3% FCE, 0.6% FCE and 0.9% FCE) until 180 day-old in this study. Meat performance measurements showed that the 0.6% FCE group of Jingyuan chickens had higher intramuscular fat (IMF), pressing loss (PL), amino acid and fatty acid contents (P < 0.05). Their breasts were collected for transcriptomic and metabolomic analyses (n=8), and 210 Differentially expressed genes (DEGs) and 29 Differentially expressed genes (DEMs) were obtained. Gene Ontology (GO) analyses of DEGs indicate multiple entries involved in IMF synthesis such as skeletal system development and cellular response to amino acid stimulation. Kyoto Encyclopedia of Genes and Genomes (GSEA-KEGG) analysis identified sphingolipid_metabolism and multiple genes affecting IMF deposition including SPHK1, CERS1, CERS6, GLB1L, SGMS2, UGT8, and UGCG. KEGG and metabolite correlation analyses of DEMs identified Aspartate, PI 38:5; PI(18:1/20:4), PI 36:3; PI(18:1/18:2), PI 36:2; PI(18:0/18:2), and PI 34:1; PI(16:0/18:1) as the likely major influences on IMF deposition in the DEMs. Correlation analysis revealed that shear force (SF) was significantly and positively correlated with Aspartate and CERS6; PL was significantly and positively correlated with SPHK1 and UGCG (P < 0.05). IMF was significantly and positively correlated with PI 34:1; PI (16:0/18:1), SPHK1 and UGCG; and flesh colour yellowness b* was significantly and positively correlated with SGMS2 (P < 0.05). The above results indicate that feeding a basal diet containing 0.6% FCE can improve the meat quality of Jingyuan chicken, which provides a theoretical basis for improving the meat quality of Jingyuan chicken.